2014
DOI: 10.1186/1478-4491-12-37
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence patterns and trends in the health care sector: 5-year monitoring of female municipal employees in the health and care sectors in Norway and Denmark

Abstract: BackgroundSickness absence is a growing public health problem in Norway and Denmark, with the highest absence rates being registered in Norway. We compared time trends in sickness absence patterns of municipal employees in the health and care sectors in Norway and Denmark.MethodsData from 2004 to 2008 were extracted from the personnel registers of the municipalities of Kristiansand, Norway, and Aarhus, Denmark, for 3,181 and 8,545 female employees, respectively. Age-specific comparative statistics on sickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…Older nurses are affected by chronic illnesses that characterize advanced age but the findings reveal that they are more committed to their work. It is surprising to have more sickness-related absence for younger staff than older staff but such a trend was also confirmed by Krane et al (2014).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Older nurses are affected by chronic illnesses that characterize advanced age but the findings reveal that they are more committed to their work. It is surprising to have more sickness-related absence for younger staff than older staff but such a trend was also confirmed by Krane et al (2014).…”
Section: Discussionmentioning
confidence: 80%
“…The findings also reveal that absenteeism is more common with younger nurses than older nurses, anecdotally attributed to lower levels of commitment by younger nurses. Previous research has reported this issue (Krane et al, 2014). Older nurses are affected by chronic illnesses that characterize advanced age but the findings reveal that they are more committed to their work.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This could explain the potential delay in RTW in the intervention group. The Norwegian welfare model, which compensates 100% of income, and regulations concerning job security may also delay RTW, especially among patients in a follow-up programme that justifies being sick-listed [33].…”
Section: Discussionmentioning
confidence: 99%